1983
DOI: 10.1093/ajcn/37.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Zinc nutritional status during pregnancy: a longitudinal study

Abstract: Dietary zinc (Zn) intake and selected biochemical indices of Zn status were studied longitudinally at monthly intervals in 46 pregnant middle-income women, 10 of whom received a daily supplement of 15 mg Zn. Mean dietary Zn intake for the nonsupplemented subjects (group A) was 11.3 +/- 4.1 mg/day (56% of the Recommended Dietary Allowances), and for the Zn-supplemented subjects (group B) was 21.7 mg/day (109% of the Recommended Dietary Allowance), including an average intake of 11.1 mg/day as supplemental Zn. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
3
4

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(99 citation statements)
references
References 38 publications
13
79
3
4
Order By: Relevance
“…The trends observed in plasma Zn andCu rn our study and elsewhere (Hambidge and Droegemueller 1974;Hambidge et al 1983;Golub et al 1984a) reinforce the suggestion that a similar mechanism(s) may be responsible for the changes in the circulating levels of both elements (Hambidge et al 1983 Hambidge et al (1983). However, Zn-deficient pregnant monkeys showed significantly reduced APA only at the end of pregnancy (Golub et al 1984a).…”
Section: Arrimals and Managementsupporting
confidence: 88%
“…The trends observed in plasma Zn andCu rn our study and elsewhere (Hambidge and Droegemueller 1974;Hambidge et al 1983;Golub et al 1984a) reinforce the suggestion that a similar mechanism(s) may be responsible for the changes in the circulating levels of both elements (Hambidge et al 1983 Hambidge et al (1983). However, Zn-deficient pregnant monkeys showed significantly reduced APA only at the end of pregnancy (Golub et al 1984a).…”
Section: Arrimals and Managementsupporting
confidence: 88%
“…(1985) supplemented low-income teenagers of Mexican descent (mean dietary intake of 10 mg Zn/d) with 20 mg Zn daily throughout pregnancy, but Zn supplementation did not affect the outcome of pregnancy compared with controls. A similar study was performed by Hambidge et al (1983) who gave a supplement of 11 mg Zn/d but found no effect on pregnancy outcome or birth weight. Tuttle et al (1 985) found no association between intravascular mass of Zn and percentilebirth-weight distribution in women taking in 9 mg Zn/d, and Campbell-Brown et af.…”
Section: S U S a N J F A I R W E A T H E R -T A I Tmentioning
confidence: 72%
“…For example, plasma Zn correlated weakly with birth weight when sampled at mid pregnancy (McMichael et al 1982), more strongly in early rather than in later pregnancy, i.e. third trimester (Neggers et al 1990), or not at all Buzina et al 1980;Hambidge et al 1983;Campbell-Brown et al 1985;Hunt et al 1985;Tuttle et af. 1985;Mahomed et al 1989).…”
Section: N F a N C Y A N D C H I L D H O O Dmentioning
confidence: 99%